Analysis of the CHN1 gene in patients with various types of congenital ocular motility disorders - Volk, Alexander E.; Fricke, Julia; Strobl, Judith; Kolling, Gerold; Kubisch, Christian; Neugebauer, Antje (Graefe's archive for clinical and experimental ophthalmology, 2010)
Mutations in the gene CHN1 have been described in autosomal dominant Duane’s retraction syndrome (DRS) and mutations have been shown to interfere with normal innervation of target eye muscles by oculomotor axons in chick embryos. We screened for CHN1 mutations in patients with various congenital ocular motility disorders.